2008
DOI: 10.1103/physrevd.77.092002
|View full text |Cite
|
Sign up to set email alerts
|

Measurements ofe+eK+Kη,K+

Abstract: This paper reports measurements of processes: e + e − → γK− → γφη and e + e − → γφπ 0 . The initial state radiated photon allows to cover the hadronic final state in the energy range from thresholds up to ≈ 4.6 GeV. The overall size of the data sample analyzed is 232 fb −1 , collected by the BABAR detector running at the PEP-II e + e − storage ring. From the Dalitz plot analysis of the K 0 S K ± π ∓ final state, moduli and relative phase of the isoscalar and the isovector components of the e + e − → KK * (892)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 181 publications
(84 citation statements)
references
References 46 publications
4
77
3
Order By: Relevance
“…The solid line represents the result of the fit described in the text. The results are consistent with those observed in our previous study of the K þ K − π 0 final state [15], also shown in Fig. 8 (circles).…”
Section: Detection Efficiencysupporting
confidence: 83%
See 3 more Smart Citations
“…The solid line represents the result of the fit described in the text. The results are consistent with those observed in our previous study of the K þ K − π 0 final state [15], also shown in Fig. 8 (circles).…”
Section: Detection Efficiencysupporting
confidence: 83%
“…12 as the points. It is consistent with our previous measurement [15] in the K þ K − η final state (circles). Again, only statistical uncertainties are shown, and they are larger than the 15%-30% systematic uncertainties.…”
Section: B Cross Section Forsupporting
confidence: 82%
See 2 more Smart Citations
“…Processes of e þ e − annihilation to the KKπ final state were studied in the DM1, DM2, and BABAR [1][2][3][4] experiments. Until recently, only the two subprocesses e þ e − → K S K AE π ∓ and K þ K − π 0 [3] were measured. The third, neutral subprocess e þ e − → K S K L π 0 is hard to study due to the complexity of K L -meson detection and identification.…”
Section: Introductionmentioning
confidence: 99%